A Hybrid Approach to Modelling ECC Risk: Effectiveness of Nonparametric Regression and MLFNN Techniques - Fei Hong Seng; Wan Muhamad Amir W Ahmad; Mohamad Nasarudin Adnan; Farah Muna Mohamad Ghazali; Nor Azlida Aleng (Galician Medical Journal)
Introduction. Early childhood caries (ECC) is a prevalent dental condition that significantly impacts children’s quality of life and is influenced by both environmental and metabolic factors. Anthropometric variables such as weight, height, and body mass index serve as indicators of overall growth and nutritional status, which are closely linked to oral health. Additionally, family size may play a role in ECC risk by influencing dietary habits and oral hygiene practices. Despite these associations, the complex and nonlinear relationships between these factors and ECC risk remain insufficiently explored.